ANALISIS PENGARUH PENERAPAN TATA KELOLA TERHADAP BIAYA HUTANG, PROFITABILITAS, Dan KAPITALISASI PASAR PADA PERUSAHAAN PUBLIK Di INDONESIA - Lule, Benny (JBE (Journal of Business and Economics); Volume 13 No.1, 2014 JBE UNKLAB, 2014)
The purpose of this study is to analyze the effect of the implementation of Good Corporate Governance on cost of debt, profitability, and market capitalization of public companies in Indonesia. Good Corporate Governance implementation is measured through scores Corporate Governance Perception Index and profitability calculated from the value of return on asset, return on equity, and net profit margin. This study uses a simple linear regression model to examine the effect of the implementation of good corporate governance to cost of debt, return on asset, return on equity, net profit margin, and market capitalization, with a dividing influence Corporate Governance Perception Index scores based on three existing categories of "Most Trusted", "Trusted", and "Quite Trusted ". The test results showed that the implementation of Good Corporate Governance on its "Most Trusted" significant negative effect on return on asset and net profit margin, as well as a significant positive effect on market capitalization. Good Corporate Governance implementation on its "Most Trusted" had no significant effect on the cost of debt and return on equity. For the implementation of Good Corporate Governance "Trusted", found that the implementation of Good Corporate Governance had significant negative effect on net profit margin and had significant positive effect on market capitalization, while the cost of debt, return on asset, and return on equity  Good Corporate Governance implementation is not significant. At Good Corporate Governance implementation in company "Quite Trusted", was not found to have a significant influence on the cost of debt, return on asset, return on equity, net profit margin, and market capitalization.